Relevansi Program Pendidikan SMK dengan Kebutuhan Dunia Kerja - Usep Kustiawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study aimed to describe the relevance of vocational-school programs to job-vacancy requirements. Proportional cluster random sampling was employed to take the sample. Data were collected using documentation, observation, questionnaire, and interview and then analyzed for their content and percentage. The results show that vocational school’s programs had relatively a high relevance to job vacancy (66%). Among graduates of vocational schools, improving skills was done through courses, experience, and information from fellows and industry. Self-study and working experience were found useful to improve knowledge.